EFFECTIVE TECHNIQUES FOR DEVELOPING READING SKILLS IN EFL CLASSES - Abduvoitov Ravshanbek (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation: Developing reading skills in EFL classes can be facilitated through the use of annotation techniques. Annotation involves actively engaging with the text by making notes, underlining key points, highlighting important information, and adding personal comments and questions in the margins.